Pseudomonas aeruginosa e Acinetobacter spp.: perfil de sensibilidade e detecção de metalo-β-lactamases no Hospital Universitário de Santa Maria - Mayer, Letícia Eichstaedt (2011)
The production of metallo-β-lactamases enzymes (MβL) by some pathogens such as Pseudomonas aeruginosa and Acinetobacter spp. clinical and epidemiological implications triggers very important because of the limited number of really effective antimicrobial treatment of infections caused by these microorganisms. A total of 114 strains were studied, 92 P. aeruginosa and 22 Acinetobacter spp. The tests were performed: antimicrobial susceptibility test, determination of minimum inhibitory concentration (MIC), phenotypic tests to detect MβL (double-disk synergy test, combined disc test and modified Hodge synergy test and polymerase chain reaction (PCR) for detection of genes MβL, and blaIMP-1 blaSPM-1. Acinetobacter spp. presented as multidrug-resistant opportunistic pathogen, and gentamicin was the antibiotic that showed greater sensitivity to this genus. High rate of strains of P. aeruginosa AmpC positive was found, and the emergence of resistance to polymyxin B, which represents the beginning of a therapeutic problem in our institution. We detected, by PCR, the presence of genes blaIMP-1 blaSPM-1and at 4.95% and 8.91% of strains, respectively. All strains with the gene blaIMP-1 were from the Acinetobacter genus. The lack of new antimicrobial agents for gram-negative non-fermenters (GN-NF) and its rapid spread multiresistant leads to therapeutic failures. Moreover, the presence of strains producing MβL in hospitals represents a serious problem for the infection control committee.